The Influence Of Learning Motivation And Campus Facilities On The Academic Performance Of Accounting Students Of Surabaya State University - Defy Syalaisha Adena Syanata; Salsabila Azzahrah (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to analyze the effect of learning motivation and computer laboratory facilities on the achievement or ability of accounting students in preparing financial systems and reports. The method used is a quantitative approach by distributing questionnaires to 50 third-semester accounting students at Surabaya State University. The data obtained were analyzed using descriptive analysis. The results of the study indicate that learning motivation has a significant effect on the academic ability of accounting students, with a t-value of 7,725 which is greater than the t table of 2,15, and a significance value of 0,000 which is smaller than 0,05. In addition, computer laboratory facilities also affect learning motivation, with a t-value of 5,472 which is greater than the t table of 2.15 and a significance value o1f 0.000. The ANOVA test shows that learning motivation and campus facilities simultaneously affect learning achievement with a significant regression value of 0.01 indicating that the alternative hypothesis is accepted and hypothesis no; is rejected. The F-value of 210,269 is much greater than the F table of 3.08, confirming that the regression model used is significant.